2022
DOI: 10.1186/s12917-022-03527-7
|View full text |Cite
|
Sign up to set email alerts
|

Guest edited collection serological study of SARS-CoV-2 antibodies in japanese cats using protein-A/G-based ELISA

Abstract: Background Little is known about the epidemic status of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in cats in Japan due to insufficiently reliable seroepidemiological analysis methods that are easy to use in cats. Results We developed a protein-A/G-based enzyme-linked immunosorbent assay (ELISA) to detect antibodies against SARS-CoV-2 in cats. The assay was standardized using positive rabbit antibodies against SARS-CoV-2. The ELIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Our findings revealed that two dogs (2/488, 0.41%) in 2020, one cat (1/355, 0.28%) in 2020, four cats (4/251, 1.6%) in 2021 were positive for anti-SARS-CoV-2 antibodies. In Japan, two previous studies have reported seroprevalence in dogs and cats: in dogs, 3 of 494 (0.61%) serum samples that were collected in 2020 were positive by ELISA [ 29 ]; and in cats, 9 of 1969 (0.48%) serum samples that were collected in 2020 were positive by ELISA [ 30 ]. In other countries and regions, seroprevalence of SARS-CoV-2 antibodies in dogs and cats by use of ELISAs or neutralization assays was reported to range from 0.01 to 16.0% and 0–18.9%, respectively [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings revealed that two dogs (2/488, 0.41%) in 2020, one cat (1/355, 0.28%) in 2020, four cats (4/251, 1.6%) in 2021 were positive for anti-SARS-CoV-2 antibodies. In Japan, two previous studies have reported seroprevalence in dogs and cats: in dogs, 3 of 494 (0.61%) serum samples that were collected in 2020 were positive by ELISA [ 29 ]; and in cats, 9 of 1969 (0.48%) serum samples that were collected in 2020 were positive by ELISA [ 30 ]. In other countries and regions, seroprevalence of SARS-CoV-2 antibodies in dogs and cats by use of ELISAs or neutralization assays was reported to range from 0.01 to 16.0% and 0–18.9%, respectively [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these three ELISA-positive samples, one possessed neutralizing antibodies against SARS-CoV-2. In cats, 9 of 1969 (0.48%) blood samples that were collected between June 2020 and July 2020 were positive by ELISA for the detection of antibodies against the S1 protein of SARS-CoV-2 [ 30 ]. Of these 9 ELISA-positive samples, one showed neutralizing activity against SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%